Presence of the Extended-Spectrum-β-Lactamase and Plasmid-Mediated AmpC-Encoding Genes in Escherichia coli from Companion Animals-A Study from a University-Based Veterinary Hospital in Taipei, Taiwan - Fang-Ling Liu; Nan-Ling Kuan; Kuang-Sheng Yeh (MDPI AG, 2021)
Extended-spectrum-β-lactamase (ESBL) and AmpC β-lactamase are two enzymes commonly found in Enterobacteriaceae that confer resistance to major antibiotics, such as third-generation cephalosporins that are widely prescribed for both human and animals. We screened for Escherichia coli producing ESBL and plasmid-mediated AmpC β-lactamase (pAmpC) from dogs and cats brought to National Taiwan University Veterinary Hospital, Taipei, Taiwan from 29 June 2020, to 31 December 2020. The genotypes and phylogenetic relatedness of these E. coli were also analyzed. Fifty samples of E. coli obtained from 249 bacterial isolates were included in this study. Among them, eight isolates had ESBL, seven had pAmpC, and one had both. Thirty-two percent (16/50) of E. coli isolates were resistant to third-generation cephalosporins. The detected ESBL genes included the blaCTX-M-1 and blaCTX-M-9 groups, and the blaCMY-2 group was the only gene type found in pAmpC. ESBL-producing E. coli belonged to the pathogenic phylogroup B2, and the sequence types (STs) were ST131 and ST1193. Three isolates were determined to be ST131-O25b, a highly virulent epidemic clone. The pAmpC-producing E. coli were distributed in multiple phylogroups, primarily the commensal phylogroup B1. The STs of the pAmpC-producing E. coli included ST155, ST315, ST617, ST457, ST767, ST372, and ST93; all of these have been reported in humans and animals. Imipenem was active against all the ESBL/pAmpC-producing E. coli; however, since in humans it is a last-resort antimicrobial, its use in companion animals should be restricted.